(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Also, each treatment of the field results in a certain stress for the plants. The natural physiological processes within a plant are hindered influencing the growth of a plant. The objectives of the paper were to determine influence of retardant, herbicide and nitrogen on growth dynamics and the development o f vegetation stages in winter wheat. The field experiments were carried out during 1998 to 1999 in Research and Training Farm "Pēterlauki" on sod calcareous medium loam, pH k c l — 7.0, humus content 20 to 25 g kg 1 in soil. The research was carried out in the fields o f intensive type of winter wheat 'Otto' with the following treatments: control; control + herbicide; control + retardant; Ngo + 70 +40 + retardants. Herbicide Dialen (2,01 ha ’) and retardant Cikocel (1,5 l haT1 ) was applied during the final stage o f tillage, when testing parted nitrogen fertiliser, the first part (N go) was used after vegetation period was resumed. The second part (N70) was applied at the beginning of stalking stage (Zadoks Growth Stage 30). The third part (N40) - during shooting into ears. The grovAng dynamics was registered by aucsinographs (designed by I.Gronskis, M.Āboliņš). This equipment allows to observe and to register the intensity o f plant growth length within twenty-four hours. Registration tapes were changed every twenty-four hours. The analysis of the results showed that the most intensive plant growth happened in the morning (9:00 - 12:00 a.m.) and in the afternoon (3:00 - 6:00 p.m.). A decrease in the growing intensity was observed during night and midday. The data show how that the growth of winter wheat was seriously hindered even 2 weeks after the treatment with agro-chemicals. Winter wheat growing in length stops in the middle of flowering stage.